Demolition of Reinforced Concrete by Steam Pressure Cracking System. (2022) - Kamiya, Osamu; Takahashi, Mamoru; Miyano, Yasuyuki; Ito, Shinichi; Murata, Kenji; Kawano, Makoto; Maisawa, Arata; Nanao, Junpei; Kazumi, Takashi; Nakatsu, Masanobu; Mizuma, Hiroyuki; Iwama, Yuichi
No abstract available